2008
DOI: 10.1186/1471-2148-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for divergent selection between the molecular forms of Anopheles gambiae: role of predation

Abstract: BackgroundThe molecular forms of Anopheles gambiae are undergoing speciation. They are characterized by a strong assortative mating and they display partial habitat segregation. The M form is mostly found in flooded/irrigated areas whereas the S form dominates in the surrounding areas, but the ecological factors that shape this habitat segregation are not known. Resource competition has been demonstrated between species undergoing divergent selection, but resource competition is not the only factor that can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 50 publications
8
146
0
Order By: Relevance
“…This may provide us a possible explanation to the paddies paradox, which describes situations where land irrigation increases mosquito populations without any increase in malaria transmission [49]. In permanent water collections, the density of predators is generally higher than in temporary water [24] and it may, therefore, contribute to reducing malaria transmission. In a time of renewed scientific and political commitment to malaria control and against biodiversity erosion, the biological conservation of predators in natural mosquito larval habitats is an obvious need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may provide us a possible explanation to the paddies paradox, which describes situations where land irrigation increases mosquito populations without any increase in malaria transmission [49]. In permanent water collections, the density of predators is generally higher than in temporary water [24] and it may, therefore, contribute to reducing malaria transmission. In a time of renewed scientific and political commitment to malaria control and against biodiversity erosion, the biological conservation of predators in natural mosquito larval habitats is an obvious need.…”
Section: Discussionmentioning
confidence: 99%
“…The backswimmer A. jaczewskii (Hemiptera: Notonectidae) is the most abundant and widespread predatory bug in mosquito larval habitats in our study area [24]. Predators were collected in Bama rice fields and were fed daily ad libitum with An.…”
Section: Materials and Methods (A) Insect Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Munga et al 2006) • Indirect effects of predator presence in larval habitat selection by molecular forms of An. gambiae (Diabate et al 2008) • Predation perception and resource abundance can modify phenotypic and life cycle traits of non-malaria mosquitoes (Beketov and Liess 2007).…”
Section: Demographic Driversmentioning
confidence: 99%
“…The S form breeds in small ephemeral pools and puddles across sub-Saharan Africa, whereas the M form exploits larger, more stable breeding sites closely associated with agricultural or urban activity in West and Central Africa. Moreover, recent field studies have suggested fitness tradeoffs apparently related to the stability of their respective breeding sites (12,13). The S form develops more rapidly and outcompetes M in predator-free space, but the M form is superior at predator avoidance, as expected in an ecotype adapted to longer-lived habitats.…”
mentioning
confidence: 99%